Optimization of disintegrant blends using Box Behnken design in the formulation of fast disintegrating tablets of diclofenac sodium - Okhuelegbe, Eraga Sylvester; Osayande, Egharevba Precious; Amara, Iwuagwu Magnus (Nigerian Journal of Pharmaceutical and Applied Science Research, 2017)
The study aimed at formulating fast disintegrating tablets of diclofenac using a blend of disintegrants and to optimize the concentrations of the disintegrants for optimal tablet properties. Seventeen batches of diclofenac sodium tablets were prepared by direct compression using 17 combinations of three disintegrants (crospovidone, croscarmellose sodium and maize starch BP) generated by an experimental Box Behnken design model and subjected to disintegration and crushing strength tests to select four optimal batches. Granules and tablets of the optimal batches were bulk-prepared and subjected to flow properties and tablet evaluations. Drug-excipient compatibility studies were also carried out using DSC and FTIR. Granules of the optimal batches were free flowing. Disintegration times of the tablets were within 60 sec and were comparable with the disintegration times of the experimental study. The tablets were of crushing strength values > 4 kp and all the batches released 100 % drug content within 30 min. Compatibility studies revealed no interaction between diclofenac sodium and the excipients used. The Box Behnken optimization of three disintegrant concentrations to produce fast disintegrating tablets of diclofenac sodium with acceptable tablet properties was successful. The different combinations of the disintegrants affected the disintegration times and crushing strengths of the tablets.